2013
DOI: 10.1182/blood-2012-07-445999
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear phagocyte miRNome analysis identifies miR-142 as critical regulator of murine dendritic cell homeostasis

Abstract: Key Points• Ex vivo isolated myeloid populations of the mononuclear phagocyte network display specific microRNA expression signatures.• miR-142-deficient mice display a reduction of splenic CD4 ϩ dendritic cells resulting in impaired priming of CD4 T-cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(147 citation statements)
references
References 50 publications
(67 reference statements)
13
131
0
2
Order By: Relevance
“…By knockdown of miR-142a-3p using 2 specific MOs, the numbers of HSCs and T cells were decreased. Interestingly, a recent report using miR-142 −/− mice also showed that more miR-142 −/− CD4 + DCs underwent apoptosis than WT ones [36]. However, defects in HSC development were not examined in that study.…”
Section: Discussionmentioning
confidence: 67%
“…By knockdown of miR-142a-3p using 2 specific MOs, the numbers of HSCs and T cells were decreased. Interestingly, a recent report using miR-142 −/− mice also showed that more miR-142 −/− CD4 + DCs underwent apoptosis than WT ones [36]. However, defects in HSC development were not examined in that study.…”
Section: Discussionmentioning
confidence: 67%
“…Consistent with the ratio of the miR-K10a 5 ′ -isomiRs detected by deep sequencing (Supplemental Table S2; Gottwein et al 2011), the miRK10a 5 ′ -isomiR is slightly more abundant in PEL cell lines than miR-K10a+1. Because of the emerging pivotal role of miR-142-3p in the vertebrate hematopoietic lineage (Nishiyama et al 2012;Mildner et al 2013;Nimmo et al 2013;Chapnik et al 2014), we assessed whether the expression of mature miR-142-3p−1 is conserved beyond mice and humans. The predicted mature miR-142-3p/−1 sequences are invariant across vertebrates (http://genome.ucsc .edu/), but less conserved portions of the pri-miRNA could lead to differences in isomiR expression.…”
Section: Mir-142-3p 5 ′ -Isomir Expression Is Conserved In Vertebratesmentioning
confidence: 99%
“…The inactivation of miR-142-3p causes defects in hematopoiesis in zebrafish (Nishiyama et al 2012) and prevents the specification of definitive hemangioblasts in Xenopus (Nimmo et al 2013). In mice, ablation of the miR-142 locus results in reduced numbers of CD4 + dendritic cells (Mildner et al 2013) and a severe impairment of platelet formation (Chapnik et al 2014). This latter phenotype is a consequence of the dysregulation of the actin cytoskeleton in megakaryocytes, the cell type responsible for platelet production (Chapnik et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1 This suggested that a signature miRNA expression for each subset might be important in establishing or maintaining the identity of each population. Focusing on miRNAs that affected DC development, Mildner et al went on to demonstrate that miR-142, originally identified to inhibit IL-6, 5 was expressed at low levels in all DC subsets but differentially affected CD4 ϩ DCs.…”
Section: Org Frommentioning
confidence: 99%
“…3,4 Three recent papers, including one in this issue of Blood, have reported that the gene encodes a protein that is essential for the processing and stability of U6 snRNA, a molecule with a crucial role in RNA splicing. 1,5,6 U6 snRNA along with 4 other snRNAs (U1, U2, U4 and U5) and their associated proteins make up the spliceosome complex that catalyses the removal of introns from mRNA. U6 is associated with the 5Ј end of the intron by base pairing before lariat formation.…”
Section: Org Frommentioning
confidence: 99%